Prospects of application of transverse seismic waves for oil and gas expolration problem-solving - Evgeniy Petrovich Kuznechenkov; Abdul-Gapur Huseynovich Kerimov; Vasiliy Ivanovich Petrenko; Vladimir Alekseevich Gridin (Наука. Инновации. Технологии)
The paper presents the results of research made in the field of longitudinal-transverse seismic prospecting to solve a wide range of oil and gas exploration problems up to the calculation of oil and gas reserves without preliminary drilling of deep wells. In particular, the mechanisms of excitation of transverse waves and the results of experimental studies conducted in the field are considered. It is noted that transverse waves that do not possess the property of phase inversion bear important information about the internal structure of the medium under study, so it becomes necessary to study them for further use to signiicantly increase the geological and economic efficiency of seismic operations. The results of research carried out with the help of various excitation sources of seismic waves are presented, as well as the experimental dependences of the intensity of transverse waves on the magnitude of the charge.